2003
DOI: 10.1007/s10019-003-0275-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of structural properties on the dye diffusion and dyeabilty of PA 6 fibres

Abstract: The relationships were investigated between the structural and dyeing properties of different structurally modified PA 6 fibers. PA 6 monofilament yarn samples were applied having different crystalline degrees and different content of alpha, respectively gamma crystalline modification. The diffusion coefficients of two different acid dyes were determined together with the content of dyestuff absorbed (under specific conditions) by fiber samples. In order to estimate colorimetry method from the viewpoint of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It has been shown that increasing the dyeing temperature above the glass transition temperature ( T g ) of polymeric fibers causes increased flexibility of the polymer segments and an increase in the amount of voids available for the dye diffusion process [ 29 ]. Therefore, it is expected that increasing the dyeing temperature would enhance the amount of absorbed dye molecules.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that increasing the dyeing temperature above the glass transition temperature ( T g ) of polymeric fibers causes increased flexibility of the polymer segments and an increase in the amount of voids available for the dye diffusion process [ 29 ]. Therefore, it is expected that increasing the dyeing temperature would enhance the amount of absorbed dye molecules.…”
Section: Resultsmentioning
confidence: 99%